Acute Myeloblastic Leukemia in Children - Hasan, Khalid; Asif, Naghmi; Hassan, Khalid; Yasmeen; Nuzhat (International Journal of Pathology, 2018)
Background: Children constitute 15-20% of Acute Myeloid leukemia cases. Children may have differentpresentations and may have different subtypes.Objective: To study the frequency of acute myeloblastic leukemia, its subtypes and clinical manifestations inchildren in a tertiary care hospitalMaterial & Methods: A Cross-sectional descriptive study was conducted at Department of Pathology PakistanInstitute of Medical Sciences from July 2007- July 2009. All patients below 15 years (n 26) with diagnosis ofAcute Myeloid leukemia were included in the study. The detailed clinical history with physical findings wasentered on specially designed performa. Subtyping of AML was done on the basis of morphology and cytochemicalstains. Results were statistically analyzed through SPSS version 14.Results: Children constituted 32% of all diagnosed cases of Most common subtype was M1 (35%) followed by M3(31%). None of the children were diagnosed as AML-M5, M7 or M0Conclusion: Total number of children among AML cases was 32%. Most patients presented with pallor, feverand bleeding. Hepatosplenomegaly was more common than lymphadenopathy. The most common subtype wasAML-M1 followed by M3